The paradoxical weakness of very short and supershort M-M multiple bonds. - Hao, Shoukang. (University of Ottawa (Canada), 1995)
This thesis deals with the syntheses and characterization of a novel series of Cr(II), as well as V(II) complexes. The strength of Cr-Cr quadruple bonds has been investigated experimentally. The Cr-Cr multiple bond of the dimeric (TAACr) $\sb2$ (TAA = tetramethyldibenzotetraaza (14) annulene) (2.1) is reversibly cleaved by pyridine to form monomeric paramagnetic octahedral (TAACrpy$\sb2\rbrack$.py (2.2). The synthesis, characterization and stability properties of a novel series of Cr(II) alkylchromates together with their transformation into unprecedented alkylidene (Schrock-type) Cr(III) species, and Cr(II) and Cr(III) metallacycles is described in chapter 4. The ability of three center chelating ligands to form dichromium units and to enforce short and very short Cr-Cr contacts is examined in a consistent series of cyclohexyl amidinate chromium complexes, with the aim of understanding the factors intrinsic in the nature of the bridging ligands which are able to promote or disfavor dinuclear aggregation and to determine the extent of intermetallic separation. The synthesis and characterization of a new series of mono-, di- and trinuclear Cr(II) borohydride compounds is described in chapter 7. The reaction of CrCl$\sb2$(TMEDA) with two equivalents of NaBH$\sb4$ afforded the thermally unstable (TMEDA)Cr(BH$\sb4)\sb2$ (7.1) which was converted by treatment with pyridine into the octahedral monomeric (Py)$\sb4$Cr(BH$\sb4)\sb2$ (7.2). Reaction of V(II) and V(III) salts with lithium amidinates formed a series of compounds where both the nuclearity and the oxidation state of the final complex were determined by the steric bulk of the substituents of the amidinate ligand. While dinuclear compounds with and without short V-V contacts have been obtained in the case of formamidinate anions, monomeric complexes and a dinuclear end-on dinitrogen complex were formed with the more bulky acetamidinate and trimethylsilyl benzamidinate. The reaction of VCl$\sb2$(TMEDA)$\sb2$ and of VCl$\sb3$(THF)$\sb3$ with two equivalents of formamidinate lithium salts respectively yielded dimeric $\rm \{\lbrack CyNC(H)NCy\rbrack\sb2V\}\sb2$ (8.2), with a very short V-V multiple bond, and $\rm \{\lbrack CyNC(H)NCy\rbrack\sb2VCl\}\sb2$ (8.4) which is also dimeric. The dinuclear structure was reversibly cleaved by treatment with pyridine forming the monomeric (CyNC(H)NCy) $\sb2$V(Py)$\sb2$ (8.3). Conversely, similar reactions with acetamidinate anion gave only the monomeric (CyNC(Mc)NCy) $\sb2$V- (THF)$\sb2$ (8.5a) and (CyNC(Me)NCy) $\sb2$VCl (8.7) respectively. Attempts to form a dinuclear structure by either removal of THF from 8.5a or reduction of 8.7 gave only the V(III) compound (CyNC(Me)NCy) $\sb3$V (8.6). Finally, reaction of VCl$\sb2$(TMEDA)$\sb2$ with two equivalents of carboxylic acid in THF in the presence of a slight excess of TMEDA at room temperature, afforded the large scale preparation of the linear V(II) trimer V$\sb3$(R$\sb2$CHCOO)$\sb6$(TMEDA)$\sb2$ (R = Ph$\sb2$CH (9.1), PhCH$\sb2$ (9.2)). Cleavage of the trimeric unit and formation of a high-spin monomeric species ((R$\sb2$CHCOO)$\sb2$V(pyridine)$\sb4\rbrack$ (9.3) was achieved upon simple treatment of 9.1 with pyridine at room temperature. The structures of 9.1 and 9.2 are demonstrated by X-ray analysis. (Abstract shortened by UMI.)
Keywords: Chemistry, Inorganic.